Bubbles and Experience: An Experiment on Speculation - Martin Dufwenberg; Tobias Lindqvist; Evan Moore (The Research Institute of Industrial Economics (IUI), 2003)
We investigate experimentally how the share of experienced traders in double-auction asset markets affects trading, in particular the occurrence of bubble-crash pricing patterns. In each session, six subjects trade in three successive market rounds and gain experience. In a fourth round, depending on the treatment, two or four experienced subjects are replaced by inexperienced subjects. The results are compared to earlier findings when all traders were either inexperienced or experienced. We explore what can be learned by analogy between these laboratory findings and the performance of naturally occurring markets.
Keywords: C92; G12; 330; Asset Market; Bubble; Crash; Experience; Experiment; Speculation; Spekulationsblase; Spekulation; Wertpapierhandel; Finanzkrise; Theorie